Isolation and identification of bacteria from four important poplar pests - Yaman, Mustafa; Erturk, Omer; Unal, Sabri; Selek, Fazil (Universidad del Valle, 2017)
In this study, the bacterial flora of important poplar pests was studied. This included Cryptorhynchus lapathi (Coleoptera: Curculionidae), Sciapteron tabaniformis (Lepidoptera: Sesiidae), Nycteola asiatica (Lepidoptera: Nolidae) and Gypsonoma dealbana (Lepidoptera: Tortricidae). The final goal was to propose alternative ecological control agents for poplar pests and decrease the undesirable effects caused by chemical pesticides in urban areas and urban forests. Forty-three bacteria were isolated from the larvae and adults exhibiting characteristic disease symptoms of these pests in five different localities for the first time. All bacterial isolates were cultured and identified using VITEK bacterial identification systems (VITEK® 2 GN ID card prod. no; 21341 and VITEK® 2 GP ID card prod. no; 21342, bioMerieux, Marcy l’Etoile). The members of the genera from Bacillaceae and Enterobacteriaceae families were most commonly isolated from both pest insects.
Keywords: Control biológico; Biological control; Bacterias entomopatógenas; Turkey.; Turquia.; Entomopathogenic bacteria; 11. Sustainability